Electrolyte and lithium ion battery

By adding composite additives to the electrolyte of lithium-ion batteries, the manganese ion dissolution problem caused by high-nickel positive electrode materials is solved, the storage gas production and open circuit voltage of the battery are improved, and the overall performance and safety of the battery are improved.

CN119786729AActive Publication Date: 2025-04-08ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411979828.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

High-nickel positive electrode materials are prone to strain and microcracks in lithium-ion batteries, resulting in the dissolution of transition metal ions such as manganese, causing problems such as gas production and short circuits, affecting battery performance and safety.

Method used

Compound additives, including diethylaminoethyl methacrylate and vinyl sulfate, are added to the electrolyte of lithium-ion batteries. These additives generate free radicals at a specific temperature, promote polymerization reaction at the positive electrode interface, reduce dissolution of manganese ions, and form oligomers on the negative electrode side to protect the negative electrode side.

Benefits of technology

It effectively improves the open circuit voltage after the battery storage gas production and storage, reduces the initial impedance, improves the overall performance and safety of the battery, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221490980000081
    Figure BDA0005221490980000081
Patent Text Reader

Abstract

The invention belongs to the technical field of power batteries, and particularly discloses an electrolyte and a lithium ion battery. The electrolyte comprises an electrolyte, a solvent and a composite additive, the composite additive at least comprises a first additive and a second additive, the first additive is diethylaminoethyl methacrylate, and the second additive is ethylene sulfate. The electrolyte provided by the invention is suitable for being matched with a ternary positive electrode material for use, can effectively improve the storage gas production of the battery and the open-circuit voltage after storage based on the synergistic effect of the first additive and the second additive, improves the comprehensive performance of the battery, and solves the gas production problem caused by the application of a high-nickel positive electrode material; therefore, the commercial large-scale popularization prospect of the high-nickel positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to an electrolyte and a lithium-ion battery. Background Art

[0002] With the continuous enrichment of lithium-ion battery application scenarios and the improvement of performance requirements, high-energy-density batteries and high-rate batteries have become the main research directions. Due to the increase in nickel content, high-nickel positive electrode materials can significantly improve the energy density of batteries. For example, the energy density of NCM811 (nickel-cobalt-manganese ratio is 8:1:1) can reach 260Wh / kg, and can reach 180Wh / kg after grouping, which is significantly improved compared to low-nickel materials. This means that at the same volume or weight, high-nickel positive electrode materials can store more electrical energy, which means longer driving range for applications such as electric vehicles. However, due to the multivalent nature and volume changes of nickel ions, high-nickel positive electrode materials are prone to strain and microcracks in secondary particles. Microcracks accelerate electrolyte penetration and transition metal dissolution, resulting in loss of active substances and degradation of battery performance, and even causing serious safety hazards.

[0003] At present, the methods to solve the dissolution of transition metal ions in high-nickel positive electrode materials are mainly concentrated on material modification and electrolyte formulation adjustment. By coating a layer of stable oxide or fluoride, such as aluminum oxide (Al2O3) and zirconium oxide (ZrO3), on the surface of the high-nickel positive electrode material, the dissolution of transition metal ions such as manganese can be effectively inhibited. These coating layers can act as a physical barrier to reduce the direct contact between the positive electrode material and the electrolyte, thereby reducing the dissolution of manganese. However, surface coating requires additional equipment and process steps, which undoubtedly increases the cost. Some existing electrolyte film-forming additives have a certain effect, but they still cannot completely solve the problems of gas production, cycle attenuation, and short circuit in high temperature environments.

[0004] Therefore, developing new lithium-ion battery electrolyte solutions to solve problems such as gas production and short circuit caused by the dissolution of transition metal ions such as manganese in high-nickel system positive electrode materials is not only related to the breakthrough and development of battery technology, but also directly affects the reliability and stability of batteries under extreme environmental conditions. Summary of the invention

[0005] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide an electrolyte and a lithium-ion battery. By adding a new additive to the electrolyte and then applying it to the lithium-ion battery, the gas production during battery storage and the open circuit voltage after storage, and the initial impedance can be improved, thereby improving the overall performance and safety of the battery, solving the gas production problem caused by the application of high-nickel positive electrode materials, and thus improving the prospects for large-scale commercialization of high-nickel positive electrode materials.

[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides an electrolyte, including an electrolyte, a solvent and a composite additive, wherein the composite additive includes at least a first additive and a second additive, wherein the first additive is diethylaminoethyl methacrylate, and the second additive is vinyl sulfate.

[0007] Furthermore, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%.

[0008] Furthermore, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.1% to 1%.

[0009] Furthermore, the mass ratio of the first additive to the second additive is 3 to 5:1.

[0010] Furthermore, the composite additive also includes a third additive, and the third additive is selected from vinylene carbonate and / or propylene sulfite.

[0011] Furthermore, the third additive includes vinylene carbonate and propylene sulfite.

[0012] Furthermore, based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.3% to 0.5%.

[0013] Furthermore, based on the total mass of the electrolyte, the mass percentage of the propylene sulfite is 0.5% to 1%.

[0014] Furthermore, the solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents.

[0015] Furthermore, based on the total mass of the electrolyte, the mass percentage of the solvent is 70% to 80%.

[0016] The present invention also provides a lithium ion battery, comprising the electrolyte as described above.

[0017] Furthermore, the lithium-ion battery comprises a positive electrode plate, the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material is Li x Ni y Co z Mn t M γ O 2-δ, wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, 0.9<x<1.1, 0.65≤y<1.0, 0≤z<0.5, 0≤t<0.5, y+z+t+γ=1, 0≤δ≤0.1.

[0018] As described above, the electrolyte and lithium ion battery of the present invention have the following beneficial effects:

[0019] 1. The present invention adds two additives to the electrolyte, namely, the first additive diethylaminoethyl methacrylate and the second additive vinyl sulfate. Among them, diethylaminoethyl methacrylate, as an alkaline additive, has the effect of removing water and acid; the lone pair of electrons on the N atom in its structure can form a weak complex with H2O / HF in the electrolyte and the decomposition product PF5 of LiPF6, effectively alleviating the occurrence of electrolyte side reactions; at the same time, at a specific temperature (such as 60°C), a small amount of vinyl sulfate will be pyrolyzed to produce DTD free radicals, and the carbon-carbon double bonds in the structure of diethylaminoethyl methacrylate can undergo polymerization reaction on the positive electrode side under the initiation of DTD free radicals, thereby improving the stability of the positive electrode interface, reducing the dissolution of manganese ions caused by microcracks in the positive electrode material, and reducing the decomposition and gas production on the positive electrode side; in addition, DTD molecules that have not formed free radicals can open the ring on the negative electrode side to form oligomers containing sulfate groups, further protecting the gas production on the negative electrode side. Therefore, the combination of the first additive and the second additive can effectively improve the gas production during battery storage and the open circuit voltage after storage, and improve the overall performance of the battery. At the same time, the present invention also limits the amount of additives in the electrolyte. Only by reasonably adjusting the amount of the first additive and the second additive within a specific range can the best balance between improving the gas production during battery storage and the open circuit voltage after storage and ensuring battery performance be found, thereby effectively improving the overall performance and safety of the battery.

[0020] 2. The present invention also introduces a third additive, vinylene carbonate and propylene sulfite, into the electrolyte, which can further improve the gas production during battery storage and the open circuit voltage after storage, thereby improving the overall performance of the battery.

[0021] 3. The electrolyte provided by the present invention is used in combination with the ternary positive electrode material to effectively form a stable interface protection layer on the positive electrode surface, thereby effectively inhibiting gas production during battery storage and the reduction of open circuit voltage during storage. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] In the present invention, unless otherwise specified, the term "plurality" means two or more.

[0024] The character " / " indicates that the objects before and after it are in an "or" relationship. For example, A / B means: A or B.

[0025] The term "and / or" is a description of the association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or, A and B.

[0026] An embodiment of the present invention provides an electrolyte, including an electrolyte, a solvent and a composite additive, wherein the composite additive includes at least a first additive and a second additive, wherein the first additive is diethylaminoethyl methacrylate (2-Diethylaminoethyl Methacrylate, DEAEMA), and the second additive is ethylene sulfate (ethylene sulfate, DTD).

[0027] The chemical formula of DEAEMA is C 10 H 19 NO2, chemical structure is:

[0028] The chemical formula of DTD is C2H4O4S, and the chemical structure is:

[0029] In lithium-ion batteries, the electrolyte plays the role of conducting ions, providing ion channels, and maintaining chemical stability. The various components in the electrolyte can be divided into electrolyte lithium salts, solvents, and additives according to their functions and dosages. Lithium salts are mainly used to provide lithium ions to form ion channels. In the entire electrochemical system of the battery, the directional movement of lithium ions and electrons generates electricity. Lithium salts have a great influence on the energy density, power density, wide electrochemical window, cycle life, and safety performance of lithium batteries; solvents are used to dissolve lithium salts and additives; additives are substances added in small amounts to the electrolyte. There are many types and each plays a different role. For example, they can have different improvement effects on the high and low temperature performance, cycle performance, and film-forming performance of the battery.

[0030] The above embodiment of the present invention adds two additives to the electrolyte, namely the first additive DEAEMA and the second additive DTD. Among them, DEAEMA, as an alkaline additive, has the effect of removing water and acid; the lone pair of electrons on the N atom in its structure can form a weak complex with H2O / HF in the electrolyte and the decomposition product PF5 of LiPF6, effectively alleviating the occurrence of electrolyte side reactions; at the same time, at a specific temperature (such as 60°C), a small amount of DTD will pyrolyze to produce DTD free radicals, and the carbon-carbon double bonds in the DEAEMA structure can undergo polymerization on the positive electrode side under the initiation of DTD free radicals, thereby improving the stability of the positive electrode interface, reducing the dissolution of manganese ions caused by micro-cracks in the positive electrode material, and reducing the decomposition and gas production on the positive electrode side; in addition, DTD molecules that have not formed free radicals can open the ring on the negative electrode side to form oligomers containing sulfate groups, further protecting the gas production on the negative electrode side. Therefore, the combination of the first additive and the second additive can effectively improve the gas production of battery storage and the open circuit voltage after storage, and improve the overall performance of the battery.

[0031] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%. If the amount of the first additive is too much, that is, exceeds the limit of 3%, it will affect the initial impedance of the battery and have a negative impact on other battery properties. On the contrary, if the amount of the first additive is too little, that is, below the critical value of 0.1%, it is impossible to effectively suppress the gas generation during battery storage and the decrease in open circuit voltage during storage.

[0032] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.1% to 1%. If the amount of the second additive is too much, that is, exceeds the limit of 1%, it will affect the initial impedance of the battery and have a negative impact on other battery properties. On the contrary, if the amount of the second additive is too little, that is, below the critical value of 0.1%, it cannot play the role of an initiator.

[0033] In some embodiments, the mass ratio of the first additive to the second additive is 3 to 5:1, which has a better effect on improving battery performance.

[0034] Therefore, reasonably regulating the dosage of the first additive and the second additive within the range defined in the above embodiment can find the best balance between improving battery storage gas production and open circuit voltage after storage and ensuring battery performance, which is also a key to improving the overall performance and safety of the battery.

[0035] In some embodiments, the composite additive further includes a third additive, and the third additive is selected from vinylene carbonate (virtual console, VC) and / or propylene sulfite (propylene sulfite, PS).

[0036] In a specific embodiment, the third additive includes vinylene carbonate and propylene sulfite.

[0037] The present invention also introduces a third additive, vinylene carbonate and propylene sulfite, into the electrolyte, which can further improve the gas production during battery storage and the open circuit voltage after storage, thereby improving the overall performance of the battery. Of course, VC and PS are added to the electrolyte as additives, and their dosage must also be reasonably controlled to avoid negative effects. Furthermore, in some embodiments, based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.3% to 0.5%, and the mass percentage of the propylene sulfite is 0.5% to 1%.

[0038] In some embodiments, the electrolyte is a lithium salt, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(trifluoromethyl)sulfonyl imide, lithium bis(trifluoromethyl)sulfonyl imide, lithium acetate, lithium methane sulfonate, or lithium trifluoromethyl sulfonate, and the mass percentage of the electrolyte is 12% to 16% based on the total mass of the electrolyte. The present invention does not limit the type of lithium salt, and a single lithium salt or a mixed lithium salt can be used. Further, in some embodiments, the lithium salt is selected from, for example, lithium hexafluorophosphate and lithium bis(trifluoromethyl)sulfonyl imide, and the mass ratio of lithium hexafluorophosphate to lithium bis(trifluoromethyl)sulfonyl imide is, for example, 13 to 14:1 to 2.

[0039] In some embodiments, the solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents, and based on the total mass of the electrolyte, the mass percentage of the solvent is 70% to 80%. Among them, carbonate solvents are selected from ethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, polycarbonate, etc., carboxylate solvents are selected from ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, etc., ether solvents are selected from ethylene glycol dimethyl ether, diethanol diethyl ether, etc., and nitrile solvents are selected from acetonitrile, propionitrile, butyronitrile, valeronitrile, etc. The present invention does not limit the type of solvent, and a single solvent or a mixed solvent can be used.

[0040] Another embodiment of the present invention provides a lithium-ion battery, including the electrolyte as described in the above embodiment / example, and also including a shell and a bare battery cell arranged in the shell, the bare battery cell including a positive electrode plate, a separator and a negative electrode plate.

[0041] In a specific embodiment, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and obtaining a multilayer laminate body by winding, and loading it into a battery casing as a bare cell. Finally, injecting an electrolyte into the casing once or multiple times so that the bare cell is completely immersed in the electrolyte. In other words, the electrolyte is injected into and fills the entire internal space of the battery, and the positive electrode sheet, the separator, and the negative electrode sheet are completely immersed in the electrolyte.

[0042] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is Li x Ni y Co z Mn t M γ O 2-δ , wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, 0.9<x<1.1, 0.65≤y<1.0, 0≤z<0.5, 0≤t<0.5, y+z+t+γ=1, 0≤δ≤0.1. Li x Ni y Co z Mn t M γ O 2-δ Belonging to the ternary positive electrode material, the electrolyte provided by the present invention is used in combination with the ternary positive electrode material to better exert the above-mentioned effect, thereby effectively inhibiting the gas production of the battery storage and the reduction of the open circuit voltage during storage. In addition, the positive electrode collector is, for example, a foil formed after surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Among them, the thickness of the positive electrode collector is, for example, 8μm to 15μm. Furthermore, in a specific embodiment, the positive electrode collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm.

[0043] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a binder and a conductive agent, and the like, and the mass ratio of the positive electrode active material, the conductive agent and the binder can be, for example, (90-98): (1-5): (1-5). The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The conductive agent is, for example, selected from any one or more of conductive carbon black (SuperP), acetylene black, carbon nanotubes or graphene.

[0044] In one specific embodiment, the positive electrode active material is, for example, LiNi 0.9 Mn 0.05 Co 0.05 O2, the binder is selected from polyvinylidene fluoride, and the conductive agent is selected from conductive carbon black. After mixing the positive electrode active material, the conductive agent and the binder, for example, in a mass ratio of 98:1:1, an organic solvent is added, and stirred under the action of a vacuum stirrer until the system is uniform to obtain a positive electrode slurry. Among them, the organic solvent is selected from N-methylpyrrolidone (NMP), for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing and slitting. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.

[0045] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is selected from, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm. In a specific embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.

[0046] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and a thickener, and the mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener can be, for example, (90-96): (1-2): (1-3): (2N5). The negative electrode active material is a compound capable of inserting and deinserting lithium ions, such as graphite, silicon oxide material (SiO x , 0<x<2) or at least one of silicon-carbon materials. The conductive agent is selected from any one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene. The binder is selected from any one or more of polyvinylidene fluoride, polyethylene oxide, polyamide, polypropylene, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene or styrene-butadiene rubber. The thickener is selected from carboxymethyl cellulose sodium (CMC-Na) and the like.

[0047] In a specific embodiment, the negative electrode active material is selected from graphite and silicon oxide material, and the mass ratio of silicon oxide material to graphite is 5:95 to 10:90, the conductive agent is selected from conductive carbon black, the binder is selected from styrene-butadiene rubber, and the thickener is selected from sodium carboxymethyl cellulose. The negative electrode active material, conductive agent, binder, and thickener are mixed in a mass ratio of 96:1:1:2, deionized water is added, and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing and slitting. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.

[0048] In some embodiments, the separator is, for example, a polyethylene (PE) film, a polypropylene (PP) film, a glass fiber film, or a composite film, and the thickness of the separator is, for example, 9 μm to 15 μm.

[0049] In some embodiments, the diaphragm includes a base film and a coating coated on the base film, wherein the base film is, for example, a PE film, a PP film, a glass fiber film or a composite film, and the thickness of the diaphragm is, for example, 8 μm to 10 μm; the coating is, for example, a nano-aluminum oxide coating, and the coating thickness is, for example, 2 μm to 4 μm.

[0050] The following specific examples are given to explain the present invention in detail. It should also be understood that the following examples are only used to explain the present invention in detail and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range according to the description herein, and are not limited to the specific values ​​​​exemplified below.

[0051] According to the types and amounts of the first additive, the second additive and the third additive in the electrolyte of Examples 1 to 10 and Comparative Examples 1 to 9 shown in Table 1, as well as the type of positive electrode active material, the electrolyte, the positive electrode sheet, the negative electrode sheet and the separator were prepared according to the following method, and then a lithium ion battery was made and performance tested. The test results are shown in Table 1.

[0052] 1. Preparation of electrolyte:

[0053] In an argon glove box with a moisture content of less than 0.1 ppm and an oxygen content of less than 0.1 ppm, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate are mixed uniformly in a mass ratio of 3:5:2 to obtain a mixed solvent, and then dry lithium hexafluorophosphate and a first additive and / or a second additive are added to the mixed solvent, and the electrolyte is obtained after mixing uniformly. In the obtained electrolyte, based on the total mass percentage of the electrolyte being 100%, the mass percentage of lithium hexafluorophosphate is 12.5%, and the mass percentage of the mixed solvent is adjusted according to the amount (i.e., mass percentage) of the first additive and the second additive.

[0054] 2. Preparation of positive electrode sheet:

[0055] After the positive electrode active material, polyvinylidene fluoride and conductive carbon black were mixed in a mass ratio of 98:1:1, N-methylpyrrolidone was added and stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil with a thickness of 13 μm, and then dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, a positive electrode sheet was obtained.

[0056] 3. Preparation of negative electrode sheet:

[0057] The negative electrode active material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil with a thickness of 13 μm, and then transferred to an oven for drying after drying at room temperature. After cold pressing and slitting, a negative electrode sheet is obtained. Among them, the negative electrode active material is a mixture of SiO and graphite, and the mass ratio of SiO and graphite is 5:95.

[0058] 4. Preparation of diaphragm:

[0059] A polyethylene film with a thickness of 8 μm was selected as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm was coated on the base film to obtain a separator.

[0060] 5. Preparation of batteries:

[0061] The positive electrode sheet, the separator, and the negative electrode sheet are wound in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a cylindrical bare battery cell is obtained. Then, it is placed in a round shell, dried in a vacuum oven, and the prepared electrolyte is injected and sealed, and the electrolyte is formed to obtain a lithium-ion battery.

[0062] 6. Performance test method:

[0063] 6.1. Direct Current Resistance (DCR) at 25°C:

[0064] Adjust the temperature of the constant temperature box to 25℃, let it stand for 10min, charge at 0.33C constant current to 4.4V, then charge at 4.4V constant voltage to 0.05C cutoff, let it stand for 30min, then discharge at 0.33C constant current to 2.8V; cycle 0.33C charge and discharge twice, record the last discharge capacity as C0; after standing for 30min, discharge at 0.33C to 50% C0, adjust the cell SOC to 50%, let it stand for 30min, record the static terminal voltage V1, discharge at 4C0 constant current for 30s, record the terminal voltage V2 and current I, calculate the DCR at the beginning of life (BOL) according to the following formula:

[0065] DCR=(V1-V2) / I.

[0066] 6.2. Gas production growth rate after storage at 60℃ for 2 months (2M):

[0067] The battery cell is charged at 0.33C constant current to 4.4V, and then charged at 4.4V constant voltage to 0.05C cut-off, and the initial volume V1 of the battery cell is recorded. Adjust the temperature of the thermostat to 60℃, transfer the battery cell to the thermostat, store for 2 months, take out and record the volume V2 of the battery cell after storage, and calculate the gas production growth rate according to the following formula:

[0068] Gas production growth rate = (V2-V1) / V1.

[0069] 6.3、60℃ Storage 2M Open Circuit Voltage (OCV):

[0070] The battery cell is charged at 0.33C constant current to 4.4V, and then charged at 4.4V constant voltage to 0.05C cutoff. The temperature of the constant temperature box is adjusted to 60℃, and the battery cell is transferred to the constant temperature box and stored for 2 months. The OCV of the battery cell after storage is recorded after being taken out.

[0071] Table 1

[0072]

[0073] From the data in Table 1, we can draw the following conclusions:

[0074] By comparing Examples 1 to 9 with Comparative Example 5, it can be seen that the combination of the first additive and the second additive can effectively improve the gas generation during battery storage and the OCV after storage.

[0075] Comparing Examples 2, 4 to 6 with Comparative Examples 1 to 2, it can be seen that as the amount of the first additive increases, the BOL DCR is slightly affected. Therefore, the amount of the first additive needs to be controlled within a reasonable range. Combined with the gas production performance and the OCV after storage, the optimal amount of the first additive is 0.5N1%. Too little or no first additive is added to the electrolyte, which cannot effectively inhibit the gas production of the battery during storage and the decrease in the open circuit voltage during storage; while too much will affect the initial impedance of the battery and have a negative impact on other battery properties.

[0076] By comparing Examples 1 to 3 with Comparative Examples 3 to 4, it can be seen that as the amount of the second additive increases, the BOL DCR is slightly affected. Therefore, the amount of the second additive needs to be controlled within a reasonable range, and the optimal amount is 0.1 to 1%. If the amount is too small or the second additive is not added to the electrolyte, it cannot play the role of an initiator; and if the amount is too large, the initial impedance of the battery will be affected, which will have a negative impact on other battery properties.

[0077] By comparing Example 5 with Examples 7 to 9 and Comparative Examples 3 to 4, it can be seen that when the mass ratio of the first additive to the second additive is 3 to 5:1, the side reactions caused by the additives are effectively suppressed, and the effect of improving battery performance is better.

[0078] By comparing Example 8 with Example 10, it can be seen that adding 0.3% VC+0.5% PS as additives to the electrolyte can further improve the gas generation during battery storage and the OCV after storage.

[0079] Comparing Comparative Examples 6 and 7, and Comparative Examples 8 and 9, it can be seen that in the system of the same positive electrode material lithium cobalt oxide, the introduction of the first additive and the second additive has a slight effect of improving the initial impedance of the battery and the gas production during storage, but it cannot effectively solve the problems of the system. At the same time, comparing Example 8 with Comparative Examples 6 and 8, it can be seen that when the positive electrode materials are lithium cobalt oxide and lithium nickel manganese oxide, the gas production during storage and the reduction of OCV during storage cannot be effectively suppressed. The electrolyte formula design of the present invention needs to match the ternary positive electrode material to better play the role of reducing the initial impedance of the battery, improving the gas production of the battery during storage and the open circuit voltage after storage, thereby improving the overall performance of the battery.

[0080] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An electrolyte, characterized in that: The invention comprises an electrolyte, a solvent and a composite additive, wherein the composite additive comprises at least a first additive and a second additive, wherein the first additive is diethylaminoethyl methacrylate, and the second additive is vinyl sulfate.

2. The electrolyte according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%.

3. The electrolyte according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the second additive is 0.1% to 1%.

4. The electrolyte according to any one of claims 1 to 3, characterized in that: The mass ratio of the first additive to the second additive is 3 to 5:

1.

5. The electrolyte according to claim 1, characterized in that The composite additive further comprises a third additive, and the third additive is selected from vinylene carbonate and / or propylene sulfite.

6. The electrolyte according to claim 5, characterized in that: The third additive includes vinylene carbonate and propylene sulfite.

7. The electrolyte according to claim 5 or 6, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.3% to 0.5%; And / or, based on the total mass of the electrolyte, the mass percentage of the propylene sulfite is 0.5% to 1%.

8. The electrolyte according to claim 1, characterized in that: The solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents; And / or, based on the total mass of the electrolyte, the mass percentage of the solvent is 70% to 80%.

9. A lithium ion battery, characterized in that: The electrolyte comprises the electrolyte described in any one of claims 1 to 8.

10. The lithium-ion battery according to claim 9, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material is Li x Ni y Co z Mn t M γ O 2-δ , wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, 0.9 <x<1.1,0.65≤y<1.0,0≤z<0.5,0≤t<0.5,y+z+t+γ=1,0≤δ≤0.1。

Citation Information

Patent Citations

  • Quasi-solid-state polymer gel electrolyte and preparation method thereof

    CN103093965A

  • Lithium ion battery electrolyte, lithium ion battery and electrochemical equipment

    CN118676437A

  • Additive agent for secondary battery, electrolytic solution for secondary battery that contains the same, and secondary battery including the same

    JP2017069204A

  • Secondary battery

    KR1020170056537A

  • Sodium secondary battery

    US20170062868A1